Jawapan

2016-07-25T19:11:09+08:00
C) n=m+4    -(1)
    m+3n=8  -(2)
    
      drpd (2) m=8-3n
     ganti (1) dlm (3)                        ganti n=3 dlm (2)
           n=8-3n+8                                    m+3(3)=8
           n=12-3n                                           m+9=8
     n+3n=12                                                     m=8-9
          4n=12÷4                                                m= -1
             n=3
                            ∴maka n=3 , m= -1

soalan (d) ada typo ke ?